Sistem Informasi Kursus Dan Sewa Lapangan Bulutangkis Pada Di Gor Griya Tahfizh Berbasis Dekstop - Hafid, Abdul; Suyanto, Suyanto (Jurnal Syntax Fusion, 2022)
Data processing for Gor Griya Tahfizh which has a lot of data including field rental, student data, customer data, honor payment data and course payment data that must be done carefully and carefully. With the many gaps and shortcomings when archiving and accessing these data caused by ineffective ways of managing data and also the insecurity of storage so that it can cause losses for owners, it is considered necessary to create a desktop-based information system application that can overcome the problem.This system is expected to be able to facilitate, speed up, and reduce errors in data input and can also present field rental data reports quickly and accurately . The use of this application can also be safer in archiving data because it is stored on the database so that it can reduce losses for owners. The app can process field rental data and badminton courses quickly, accurately and securely. Data search and presentation of reports can also be done quickly and easily, making it easier for store owners to conduct supervision in various transactions.